Desain Pembangunan Budaya Tanggung Jawab pada Anggota Remaja Masjid - Ani Rufaidah (STID Al-Hadid, 2022)
To support the achievement of the mosque youth goal’s program, responsibility is important to be owned by members and developed in so that members will carry out all the mandates given as well as possible. The study of cultural development on mosque youth members is pretty much done but they didn't focus on formulating how to build a culture of responsibility and tend to be descriptive. This study will formulate a design for developing responsibility’s culture for mosque youth members with primary and secondary mechanisms perspectiv based on Edgar Schein's theory. This is basic research and expected to be a reference in responsibilty’s culture development for youth mosque members. The primary mechanisms include: (1) Leaders pay attention to and control the responsibilities of members; (2) Leaders remind members of responsibilities in crisis situations; (3) Responsible use of resources; (4) Be a model and teach to be responsible; (5) Responsibility as reward and punishment criteria; (6) Responsibilities as criteria for recruitment and members staffing. While the secondary mechanisms include: (1) Organizational design supports a culture of responsibility; (2) Organizational systems and procedures that emphasize responsibility; (3) organizational rituals to strengthen the culture of responsibility; (4) Affixes related to the culture of responsibility; (5) Stories of responsible figures; (6) The philosophical statements and character of the youth members of the mosque are the responsibility.